A new concept for improving the structural resilience of lap-welded steel pipeline joints. (February 2022) - Keil, Brent D.; Fappas, Dimitris; Gobler, Fritz; Sarvanis, Gregory C.; Chatzopoulou, Giannoula; Lucier, Gregory; Mielke, Richard D.; Karamanos, Spyros A.
Abstract: Lap-welded steel joints are widely used in steel pipelines for water transmission, and their structural resistance is essential for safeguarding pipeline integrity and functionality after severe earthquakes or other geohazards. These pipelines are thin-walled with a diameter-to-thickness ratio ranging between 100 and 240 and are susceptible to buckling. The present paper is part of a longtime research project on the structural performance of lap-welded steel pipeline joints subjected to severe inelastic deformations, motivated by the need of pipeline safety in geohazards areas. The work described in the present paper focuses on the mechanical behavior, analysis, and design of a new seismic resistant lap-welded joint which was developed to improve the structural performance of lap-welded steel pipelines. Analysis consists of extensive finite element simulations, supported by a series of special-purpose full-scale experiments, on the mechanical response of the new lap-welded joints subjected to severe structural (axial and bending) loading conditions. The proposed joint consists of the standard lap weld configuration, enhanced by a small geometric projection introduced at a specific location near the field-applied fillet weld. The numerical and experimental results demonstrate that under severe compressive loading, this enhancement of the standard lap-welded joint results in consistent and preferential buckling of the steel pipe cylinder and not the lap-welded joint. The proposed joint effectively allows for the steel pipeline resistance to not be limited by the compression capacity of the standard lap-welded joint and offers an efficient, reliable, and economical solution for lap-welded joints in steel water pipelines constructed in geohazard areas. Highlights: A small projection is introduced enhancing the standard lap-welded joint. The projection prevents the buckle to occur at the bell or at the field weld. Optimum amplitude of the projection is determined with FE simulations. Optimum amplitude has been validated via experiments on 24′′size specimens. The new concept increases resilience of lap-welded pipelines in geohazard areas.